Analysis of management accounting information on competitive advantage in servitized manufacturing firms with decision making effectiveness and innovation by mediation - Nugroho, Andri Setyato; Purwohedi, Unggul; Prihatni, Rida (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This study aims to test and analyze the effect of MAI on CA in servitized manufacturing firms, MAI on DME, DME on CA, and the effect of MAI on CA by DME mediation, the effect of MAI on IN, IN on CA, and the effect of MAI on CA by IN mediation. The research method uses a quantitative approach with a convenience sampling. The primary research data was collected through questionnaires obtained from a total sample of 82 manufacturing companies in the Surabaya Industrial Estate Rungkut (SIER) area, Surabaya, East Java. The research used data analysis techniques in the form of descriptive statistical analysis and statistical analysis through PLS-SEM on WarpPLS 7.0. The results of the study concluded that (1) MAI on CA; (2) MAI on DME; (3) DME on CA; (4) DME mediates MAI on CA; (5) MAI on IN; (6) IN on CA; and (7) IN mediates MAI on CA, all result has a significant positive effect. This research contributes to parallel research and contributes to contingency theory. In addition, this research has implications for manufacturing companies to be able to optimize management accounting information in an effort to be able to competitively which can improve business performance compared to its competitors